2023
DOI: 10.3390/s23031320
|View full text |Cite
|
Sign up to set email alerts
|

A Classification Method of Point Clouds of Transmission Line Corridor Based on Improved Random Forest and Multi-Scale Features

Abstract: Classification of airborne laser scanning (ALS) point clouds of power lines is of great importance to their reconstruction. However, it is still a difficult task to efficiently and accurately classify the ground, vegetation, power lines and power pylons from ALS point clouds. Therefore, in this paper, a method is proposed to improve the accuracy and efficiency of the classification of point clouds of transmission lines, which is based on improved Random Forest and multi-scale features. The point clouds are fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Then, the details of the model are optimized, the geometric shape is smoothed, and the position relationship is calibrated. Ensure that the model is in line with the actual transmission line condition, and can truly reflect the on-site condition [3][4] . The preliminary GIM model of the transmission line is shown in Figure 2 (a) Preliminary GIM model of transmission line (b) Preliminary GIM model of tower…”
Section: Preliminary Construction Of Gim Model Of Transmission Linementioning
confidence: 99%
“…Then, the details of the model are optimized, the geometric shape is smoothed, and the position relationship is calibrated. Ensure that the model is in line with the actual transmission line condition, and can truly reflect the on-site condition [3][4] . The preliminary GIM model of the transmission line is shown in Figure 2 (a) Preliminary GIM model of transmission line (b) Preliminary GIM model of tower…”
Section: Preliminary Construction Of Gim Model Of Transmission Linementioning
confidence: 99%
“…This is a model that helps to represent a surface from points with discrete spatial distribution. We can represent the surface in terms of adjacent triangles that do not overlap [7]. In each triangle, the surface is represented by a plane.…”
Section: A Creating Tin and Noise Removingmentioning
confidence: 99%
“…In the article [7], the authors use RF algorithm (Random Forest) and multi-scale cluster to perform power line classification. The authors have shown that it is necessary to distribute the features of points in the point cloud to perform the classification problem in different rules.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, automatic extraction algorithms are susceptible to complex topology structures and system noise. Studies showed that the use of multi-scale features can eliminate or mitigate the impact of noise and high similarity between different objects on extraction accuracy and robustness [9][10][11][12][13]. However, there are few reports on how to use multi-scale geometric features and perform fusion and quantitative evaluation of these features to solve the problems in insulator extraction.…”
Section: Introductionmentioning
confidence: 99%